3D numerical analysis of 2D profile bending with the torque superposed spatial bending method - Hudovernik, Matej (Strojniški vestnik, 2013)
Engineering research, in the field of light weight design, is strongly oriented towards the development of new high strength materials and innovative forming methods, capable of withstanding limitations with regard to the wide variety of technological and economical aspects. Cost effective lightweight construction, in addition to the reduction of energy/material consumption and overall reduction of weight, also strongly depends on stability, continuity and robustness of production processes. Kinematic solutions for the production of spatial designed structures, in terms of 3D bending of profiles and tubes, show great potential in an increase of efficiency in the field of light weight design. The Torque Superposed Spatial bending method - TSS, developed at the Institute of Forming Technology and Lightweight Construction, Technische Universität Dortmund, represents an innovative, robust and cost effective technical solution for 2D and 3D bending of tubes and profiles and offers a wide spectrum of capabilities, such as process continuity, parameter adaptation and flexibility for spatial bending of profiles with arbitrary cross-sections. In this paper, an introduction to 3D numerical analysis of the 2D profile bending method using TSS method is introduced and presented. The first objective of the work is to establish validity of the numerical model for the bending parameters, such as the bending force and bending momentum. Secondly, further investigations of the state of stresses and strains during load and unload conditions were performed. These are important for any further analysis and understanding of spring-back, residual stresses and cross section deformation of the profiles. The numerical simulations are performed with the use Abaqus software code, with elastic plastic material characteristics, and are, for the purpose of validation, compared to experimental data.
Keywords: 2D profile bending; 2D-krivljenje profilov; 3D FEM analysis; 3D MKE; numerical simulation; numerična simulacija; prostorska superpozicija navora; superposed spatial torque; TSS; upogibanje